Diasporas, Development and Peacemaking in the Horn of Africa - Laakso, Liisa; Hautaniemi, Petri (Africa Now, 2014)
Exiled populations, who increasingly refer to themselves as diaspora communities, hold a strong stake in the fate of their countries of origin. In a world becoming ever more interconnected, they engage in 'long-distance politics' towards, send financial remittances to and support social development in their homelands. Transnational diaspora networks have thus become global forces shaping the relationship between countries, regions and continents. This important intervention, written by scholars working at the cutting edge of diaspora and conflict, challenges the conventional wisdom that diaspora are all too often warmongers, their time abroad causing them to become more militant in their engagement with local affairs. Rather, they can and should be a force for good in bringing peace to their home countries. Featuring in-depth case studies from the Horn of Africa, including Somalia and Ethiopia, this volume presents an essential rethinking of a key issue in African politics and development.